Problems of Peer-to-Peer Lending (P2PL) in Indonesia from an Islamic Law Perspective - Ermanita Permatasari; Siti Fatimah; Nuri Safitri; Roma Wijaya (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
In today's digital era, online platforms have revolutionised access to essential services, including financial transactions such as borrowing money. This research investigates the proliferation of online lending services, which provide easy access to funds with minimal prerequisites, thus facilitating widespread participation. However, the exponential growth of online loans also amplifies associated risks for all stakeholders involved. This study employs an empirical-juridical approach to examine the implementation of online lending and borrowing services, evaluating both their benefits and drawbacks. The research utilises data from Financial Services Authority Regulation Number 77/POJK.01/2016, focusing on its impact on consumer protection within the online lending sector. By analysing regulatory frameworks and empirical data, this study aims to enhance public awareness regarding the legal provisions and risks associated with online financial transactions. The findings underscore the necessity of informed decision-making among borrowers and lenders alike, promoting a balanced approach to financial inclusivity and risk management in the digital economy. Ultimately, this research contributes valuable insights into the evolving landscape of online lending practices and their implications for regulatory policy and consumer protection in Indonesia